2021
DOI: 10.3390/app11114847
|View full text |Cite
|
Sign up to set email alerts
|

A GIS-Based Spatial Analysis Model Approach for Identification of Optimal Hydrotechnical Solutions for Gully Erosion Stabilization. Case Study

Abstract: The accentuated degradation of agricultural lands as a result of deep erosion processes is the main problem identified in abandoned agricultural lands under the rainfall intensities, increasing number of hot days, indirectly under the impact processes derived from them (soil erosion, vegetation drying, etc.), as well as inadequate or poor management policies implemented by local authorities. The present study aims to develop and present a methodology based on GIS spatial analysis to choose the best hydro-ameli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…In previous studies, various areas that were susceptible to degradation and desertification were identified, most of them due to climate changes that cause frequent dry events such as those in the Dobrogea Plateau and the eastern Romanian Plain [68,69], and in other areas due to soil erosion and landslides such as those in the Moldavian Plateau [70,71] and some areas in the Transylvanian Depression [72,73]. Also, soil erosion was identified in various areas of the Dobrogea Plateau [74], a phenomenon potentiated by overgrazing [75,76].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, various areas that were susceptible to degradation and desertification were identified, most of them due to climate changes that cause frequent dry events such as those in the Dobrogea Plateau and the eastern Romanian Plain [68,69], and in other areas due to soil erosion and landslides such as those in the Moldavian Plateau [70,71] and some areas in the Transylvanian Depression [72,73]. Also, soil erosion was identified in various areas of the Dobrogea Plateau [74], a phenomenon potentiated by overgrazing [75,76].…”
Section: Discussionmentioning
confidence: 99%
“…The Topolovăţu Mic hydrotechnical node is part of the hydrotechnical planning: "The Double Timis , -Bega Connection", which was conceived by the Dutch engineer Maximilian Emmanuel de Fremaut and built in 1758 [27,32]. In order to defend the municipality of Timisoara from high waters, the dam from Topolovăţ controls, on Beghei, a maximum flow of 40 m 3 /s, and the extra flow is discharged in Timis , through a channel of 5.5 km long.…”
Section: Topolovăţu Mic Hydrotechnical Nodementioning
confidence: 99%
“…Integrated analysis based on hydraulic modelling and nonstructural design [116,[124][125][126][127][128][129][130][131][132] Monitoring topography Repeated UAV surveys provide a unique opportunity to investigate geomorphic changes that result from an extreme event. The joint use of UAV and GIS methodologies proved to be a useful tool, not only for the rapid analysis of spatial data from a large population of sinkholes but also for providing an objective approach with consistent measurement and calculation processes.…”
Section: Monitoring Erosion or Landslide Activitymentioning
confidence: 99%